2019
DOI: 10.18488/journal.99.2019.62.54.60
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Assessment of Syphilis Seroprevalence among Pregnant Women, Cape Coast, Ghana

Abstract: This is a hospital-based cohort study, which aimed at assessing the seroprevalence of syphilis among pregnant women who sought antenatal care at the Cape Coast Metropolitan Hospital (CCMH). We retrospectively analyzed secondary data of 2,640 term pregnant women,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
1
Order By: Relevance
“…Congenital syphilis is the ramifications of maternal syphilis that is undiagnosed, inadequately treated, or untreated [ 35 ]. The 0.8% seroprevalence in our study is lower than reported in similar research works in Ghana, Nigeria, Ethiopia, and Sudan [ 36 40 ] but higher than 0.24% obtained in Ho, Ghana, and 0.19% in Portugal [ 32 , 35 ]. Despite the low prevalence in our study, it still remains a public health concern due to its adverse effects on newborn.…”
Section: Discussioncontrasting
confidence: 80%
“…Congenital syphilis is the ramifications of maternal syphilis that is undiagnosed, inadequately treated, or untreated [ 35 ]. The 0.8% seroprevalence in our study is lower than reported in similar research works in Ghana, Nigeria, Ethiopia, and Sudan [ 36 40 ] but higher than 0.24% obtained in Ho, Ghana, and 0.19% in Portugal [ 32 , 35 ]. Despite the low prevalence in our study, it still remains a public health concern due to its adverse effects on newborn.…”
Section: Discussioncontrasting
confidence: 80%